High-temperature plasmas of interest to astrophysics and fusion reactors - Grilo, Filipe Ventura (2020)
Physical interpretations of astrophysical observations of hot plasmas are made with models based on atomic data, being most of this from theoretical calculations of atomic structure and collisional processes. Recently, discrepancies have been arising between observations, laboratory experiments and the theoretical models. Among the several collision processes included in these theoretical plasma models, Dielectronic Recombination (DR) constitutes an essential process for the plasma ionic balance. In this work, measurements of DR of Fe XVII and Kr XXVII from EBIT, as well as charge state dynamics simulations of the experiments and new FAC, MBPT and MCDF cross section calculations, are presented. Moreover, experimental DR rates were extracted and compared with widely used atomic databases. Several discrepancies between the experimental data, the new calculations and existing atomic databases were found and discussed. This dissertation provides new DR atomic data for Fe XVII that is relevant for charge state balance calculations and spectral simulation of astrophysical plasmas. Furthermore, new data of DR of Kr XXVII is also presented, which can have future implications for the development of diagnostic tools that are currently in need for the development of future fusion reactors.